Can a corporate well-being programme maintain the strengths of the healthy employee in times of COVID-19 and extensive remote working? An empirical case study. (European Journal of Government and Economics, 2022)
The COVID-19 pandemic and the increase of working-from-home have drastically changed many aspects of work life, causing very negative effects on employees' physical and psycho-social well-being. Healthy organisations have healthy employees, who have at least five psycho-social strengths of engagement, self-efficacy, resilience, optimism and hope, which are reinforced by physical activity, relating to each other in a positive way and leading to numerous benefits for the company. These strengths are being weakened by the pandemic, and the aim of this empirical study is to analyse through a case study the effects of an updated corporate wellness programme in times of pandemic on these strengths of the healthy employee. The sample was of 251 employees, 91 women and 160 men. The instruments used were the International Physical Activity Questionnaire and the adaptation of the Healthy and Resilient Organization questionnaire. The results indicated that workers with high physical activity, higher seniority, well guided by supervisors, as well as a comprehensive (multi-component) well-being programme, not only physical but also psycho-social, and with the use of different digital tools (an App is not enough), can mitigate these negative effects. Whereas companies are grappling with reduced employee engagement among other harmful psychosocial and physical effects, this case study suggests that a good corporate well-being programme could help mitigate these detrimental consequences for their workforce and be helpful for the company to adapt to this rapidly changing workplace.